2020
DOI: 10.1002/cam4.3258
|View full text |Cite
|
Sign up to set email alerts
|

High mutation burden of circulating cell‐free DNA in early‐stage breast cancer patients is associated with a poor relapse‐free survival

Abstract: Background High tumor mutation burden is shown to be associated with a poor clinical outcome. As the tumor‐derived fraction of circulating cell‐free DNA (cfDNA) is shown to reflect the genetic spectrum of the tumor, we examined whether the mutation burden of cfDNA could be used to predict the clinical outcomes of early‐stage breast cancer (BC) patients. Methods We selected a set of 79 Finnish early‐stage BC cases with a good prognosis based on traditional prognostic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, ROC curve analysis indicated that the afore mentioned tumor-specific variants do not support prognostic ability for RFS (AUC 0.521, p = 0.748). 85 In another primary study, it was shown that the total number of somatic mutations and the mean frequency of allelic variants in ctDNA were significantly higher in patients with disease progression compared to patients with stable disease. 26 In another, it was verified that DFS was significantly worse in ctDNA positive patients (VAF > 0.1%) than in those with negative ctDNA (p < 0.001).…”
Section: Resultsmentioning
confidence: 97%
“…However, ROC curve analysis indicated that the afore mentioned tumor-specific variants do not support prognostic ability for RFS (AUC 0.521, p = 0.748). 85 In another primary study, it was shown that the total number of somatic mutations and the mean frequency of allelic variants in ctDNA were significantly higher in patients with disease progression compared to patients with stable disease. 26 In another, it was verified that DFS was significantly worse in ctDNA positive patients (VAF > 0.1%) than in those with negative ctDNA (p < 0.001).…”
Section: Resultsmentioning
confidence: 97%
“…Despite the scattered results of cfDNA TMB, it may still be clinically useful since TMB has shown promising results for predicting response and prognosis of lung cancer patients treated with immunotherapy (Gandara et al 2018 ; Khagi et al 2017 ). Regarding other cancer types, one study on breast cancer patients treated with surgery and radiotherapy has shown an association between the number of cfDNA variants and relapse-free survival (Kujala et al 2020 ). Jaiswal et al ( 2014 ) found that the presence of a somatic mutation in peripheral blood cells was associated with an increase in all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the scattered results of cfDNA TMB, it may still be clinically useful since TMB has shown promising results for predicting response and prognosis of lung cancer patients treated with immunotherapy (Gandara et al 2018;Khagi et al 2017). Regarding other cancer types, one study on breast cancer patients treated with surgery and radiotherapy has shown an association between the number of cfDNA variants and relapse-free survival (Kujala et al 2020). Jaiswal et al (2014) found that the presence of a somatic mutation in peripheral blood cells was associated with an increase in all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%